Academic Writing Skills in Islamic Higher Education: Engaging Inquiry-based Learning Methods - Syahraini Tambak; Mardhiyah Hayati; Mujahid Mustafa Bahjat (Jurnal Pendidikan Agama Islam Al-Thariqah, 2023)
The aims of this research is to analyze the effect of the inquiry-based learning method on the academic writing skills of students of the Islamic Religious Education Study Program. This type of research is quantitative with a correlation approach. This study involved 371 samples with data collection techniques using questionnaires and analyzed using the normality test and hypothesis testing which consisted of the T test, one way ANOVA and linear regression. The results of the study indicate that there are differences in the use of the lecturer's inquiry-based learning method and writing skills based on gender, semester and class. There is no difference in the use of the lecturer's inquiry-based learning method and academic writing skills based on the origin of the school and the occupation of the parents. Other results show that there is an influence of the inquiry-based learning method on the academic writing skills of students of the Islamic Religious Education Study Program with a significance value of 0.000. The magnitude of the effect is strong (0.710 or 71%). This study concluded that the inquiry-based learning method had an effect on the academic writing skills of students of the Islamic Religious Education Study Program. This research has implications for the theory of academic writing skills in Islamic Higher Education